Simulation Analysis on the Potential Application of Matched Bandstop to Bandpass Filter in Filter Integrated SPDT Switch Design - Zobilah, A. M.; Shairi, N. A.; Zakaria, Z.; Ahmad, B. H.; Zahari, M. K.; Wong, P. W. (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
This paper presents the simulation analysis on the potential application of matched bandstop to bandpass filter in filter integrated switch (FIS) design. The FIS consists of matched band-stop to bandpass filter integrated with single-pole-double-throw (SPDT) switch. The proposed design was demonstrated for 2.45 GHz applications in wireless data communication systems such as Bluetooth and Zigbee. The filter was based on L-shape lossy resonator, which can provide an absorptive feature. PIN diodes were used as switching elements for the SPDT switch and to reconfigure between band-stop and bandpass responses. Therefore, the key advantages of the proposed design are high isolation and good return loss at both ON- and OFF-state ports. As a result, the simulation showed the followings: higher than 10 dB of return loss and greater than 25 dB of isolation at the operation frequency.